Amperometric Bioelectronic Tongue for glucose determination - Yazan Al-Issa; John Njagi; Stephanie C. Schuckers; Ian I. Suni (Sensing and Bio-Sensing Research, 2015)
An amperometric Bioelectronic Tongue is reported for glucose determination that contains eight sensor electrodes constructed using different metal electrodes (Pt, Au), oxidoreductase enzymes (glucose oxidase, ascorbate oxidase, uricase), and membrane coatings (Nafion, chitosan). The response to varying concentrations of glucose, ascorbic acid, uric acid, and acetaminophen was tested for two models, concentration determination by current density measurements at individual electrodes and concentration determination by a linear regression model for the entire electrode array. The reduced chi-squared for the full array model was found to be about one order of magnitude lower than that for the individual-electrode model. Discrimination of glucose from chemical interference by the other three species is accomplished through a combination of enzyme catalysis, metal electrocatalysis, and membrane surface charge. The benefit of incorporating enzyme electrodes into the sensor array is illustrated by the lower correlation coefficients between different enzyme electrodes relative to non-enzyme coated electrodes. This approach can be more generally applied to detection of other substrates of oxidoreductase enzymes.